The Effect of Leadership, Commitment, and Adversity Quotient on Employee Performance at PT Mitra Integrasi Informatika - Risfa Dewi; Setyani Dwi Lestari; Aninda Zakia Arafa; Fenti Sofiani (International Journal of Organizational Business Excellence, 2023)
Companies must have a competitive edge that can only be achieved through productivity, innovation, creativity, and consistently passionate and loyal employees to compete in a similar industry. Appropriate human resource management concepts and techniques should be also applied to ensure excellent job performance, effective leadership, good employee engagement, adversity quotient, and a supportive work environment. The research aimed to analyze the effect of leadership, commitment, and adversity quotient on the performance of employees of PT Mitra Integrasi Informatika. The research used a quantitative method by using questionnaire to collect data. The population is selected from employees in this company. By using Slovin formula, the number of samples needed was 109 respondents. The questionnaire was distributed to the target respondents by using simple random sampling technique. Multiple regression analysis technique was applied to all collected data by using Statistical Product and Service Solutions (SPSS) program version 22. The findings indicate that leadership, commitment, adversity quotient have a positive and significant effect on employee performance.